2011
DOI: 10.1161/circheartfailure.110.960179
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Rosiglitazone Treatment on Renal Handling of Salt and Water in Rats With Volume-Overload Congestive Heart Failure

Abstract: Background-The side effects of fluid retention and edema of the thiazolidinedione (TZD) class of peroxisome proliferator-activated receptor-␥ agonists limit their use in patients with congestive heart failure (CHF). The present study aims to explore whether chronic treatment with the TZD compound rosiglitazone (RGZ) is associated with worsening of salt and water retention in male Sprague-Dawley rats with aorto-caval fistula, an experimental model of volume-overload CHF. Methods and Results-The effects of oral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
(39 reference statements)
2
7
0
Order By: Relevance
“…The present study extends our previous reports 21 In rats with ACF, RGZ did not exacerbate Na+ and water retention or cardiac dysfunction. Rather, it improved renal salt handling and ANP sensitivity, possibly through the enhancement of tubular post-cGMP signalling.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present study extends our previous reports 21 In rats with ACF, RGZ did not exacerbate Na+ and water retention or cardiac dysfunction. Rather, it improved renal salt handling and ANP sensitivity, possibly through the enhancement of tubular post-cGMP signalling.…”
Section: Discussionsupporting
confidence: 92%
“…The present study extends our previous reports and provides novel information on the effects of prolonged RGZ treatment on renal haemodynamics and excretory functions in rats with ‘compensated’ CHF. Previously, we have demonstrated that chronic RGZ treatment caused no further increase in plasma volume compared with vehicle‐treated CHF rats, no increase in renal expression of Na + transport‐linked channels/transporters, no association with any deterioration in selected biomarkers of CHF and did not result in worsening of the cardiac and renal status.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Goltsman et al [43] recently examined the effect of rosiglitazone administered at a dose of 30 mg/kg/day for 4 weeks in rats with congestive heart failure (CHF) induced by aortocaval fistula. Surprisingly, rosiglitazone improved sodium excretion which was impaired in CHF rats.…”
Section: Effect Of Pparγ Agonists In Heart Failurementioning
confidence: 99%
“…Recently, we reported that chronic treatment with the PPARγ-agonist rosiglitazone (RGZ) improved the natriuretic and diuretic responses to extracellular fluid volume expansion in rats with aorto-caval fistula, an experimental model of volume-overload CHF [1]. In the present study we explored whether RGZ improves also the natriuretic/diuretic response to ANP in rats with experimental CHF.…”
Section: Introductionmentioning
confidence: 96%